2014
DOI: 10.3109/02713683.2014.898310
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Thickness in Patients with Chronic Heart Failure Analyzed by Spectral-Domain Optical Coherence Tomography

Abstract: Our results suggest that SFCT is lower in eyes of CHF patients compared to age- and gender-matched healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 42 publications
1
48
1
3
Order By: Relevance
“…The seemingly obvious connection between the vascular components of the choroid and other vascular beds of the body has produced a number of studies on the relationship between SFCT and various cardiovascular diseases. Ahmad et al [23] showed that patients with coronary artery diseases had a thinner macular choroid than controls and Altinkaynak et al [24] showed that patients with congestive heart failure presented lower SFCT compared to age-and gender-matched controls. A single study evaluated the relationship between hypercholesterolemia and SFCT, showing SFCT to be significantly higher in patients with increased total cholesterol compared to controls [25].…”
Section: Discussionmentioning
confidence: 99%
“…The seemingly obvious connection between the vascular components of the choroid and other vascular beds of the body has produced a number of studies on the relationship between SFCT and various cardiovascular diseases. Ahmad et al [23] showed that patients with coronary artery diseases had a thinner macular choroid than controls and Altinkaynak et al [24] showed that patients with congestive heart failure presented lower SFCT compared to age-and gender-matched controls. A single study evaluated the relationship between hypercholesterolemia and SFCT, showing SFCT to be significantly higher in patients with increased total cholesterol compared to controls [25].…”
Section: Discussionmentioning
confidence: 99%
“…Severe hypertensive retinopathy with serous retinal detachments has been associated with hypertensive choroidopathy and choroidal thickening [11]. Uncomplicated hypercholesterolemia without other vascular disease has been associated with choroidal thickening [12], whereas cigarette smoking [13,14], ocular ischemic syndrome [15], chronic heart failure [16], and systemic essential hypertension [17,18] have been linked to a thinner choroid. Carotid artery stenosis [19,20] and diabetes without diabetic retinopathy [21,22] have shown contradictory associations with CTh.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the EDI-OCT technique is accepted as a useful tool to study the morphologic changes associated with many choroidal disorders. [8][9][10][11][18][19][20][21][22][23] Decreased choroidal thickness has been observed in age-related macular degeneration, 19 glaucoma, 20 and high myopia. 9 Increased choroidal thickness has been observed in central serous chorioretinopathy, 20 polypoidal choroidal vasculopathy, 21 and choroidal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][18][19][20][21][22][23] Decreased choroidal thickness has been observed in age-related macular degeneration, 19 glaucoma, 20 and high myopia. 9 Increased choroidal thickness has been observed in central serous chorioretinopathy, 20 polypoidal choroidal vasculopathy, 21 and choroidal neovascularization. 22 Moreover, choroidal thickness measurements represent a potential parameter to better follow choroidal diseases and their response to treatment, including central serous chorioretinopathy, 20 idiopathic choroidal neovascularization, 23 and exudative age-related macular degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation